Antibiotic Resistance Changes in Gram-Positive Bacteria from Urine Cultures: Development Analysis in a Health Area of South-East Spain - Luis Fernández-Espigares; Itahisa Hernández-Chico; Manuela Expósito-Ruiz; Antonio Rosales-Castillo; José María Navarro-Marí; José Gutiérrez-Fernández (Antibiotics, 2023)
This study analyzed the epidemiology and antibiotic susceptibility profile of significant bacteriuria and assessed the impact of adopting EUCAST criteria on antibiotic resistances. A systematic review was performed on publications in English or Spanish between 1 January 2010 and 30 June 2021 on the susceptibility of Gram-positive bacteria isolated in urinary samples in Europe. A retrospective descriptive study was also conducted on the results of 21,838 urine cultures with presumptive urinary tract infection (UTI) obtained during the past five years by the Department of Microbiology of the Virgen de las Nieves University Hospital (Granada, Spain). The activity of various antibiotics was determined, differentiated among various populations, and interpretations compared according to the application of EUCAST or CLSI criteria. Among 21,838 cases of significant bacteriuria, 27.69% were by Gram-positive bacteria, which were Enterococcus faecalis in 19.04% and Enterococcus faecium in 3.92%. The susceptibility profile remained stable for most antibiotics except for levofloxacin for E. faecalis and Staphylococcus aureus and nitrofurantoin for E. faecium. The resistance of Enterococcus spp. and Staphylococcus spp. to glycopeptides was exceptionally low in our setting. No significant difference in the prevalence of methicillin-resistant Staphylococcus aureus was observed between hospital (26.67%) and community (28.85%) samples. Resistances in our local setting remain stable and appear to be lower than reported in other studies. The adoption of EUCAST vs. CLSI criteria did not produce a general change in resistance rates. Findings suggest the need to revise certain empirical criteria, such as aminoglycoside synergy for Enterococcus and for community-origin S. aureus.